2022
DOI: 10.3389/fpsyg.2022.819874
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Stress-Related Couple Processes During the COVID-19 Pandemic and Lockdown: A Longitudinal Dyadic Perspective

Abstract: In March 2020, the World Health Organization declared the disease caused by SARS-CoV-2 coronavirus “pandemic.” To reduce the risk of contamination, many countries have ordered a lockdown characterized by social distancing and restrictive isolation measures. While the lockdown has proven to be quite effective in terms of physical health, little is known about its impact on couple satisfaction in a dyadic perspective. The current research was a 4-waves longitudinal study (i.e., from March to July 2020) with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…Our first hypothesis was disconfirmed: There were no dramatic negative changes in couple satisfaction during 1 year of the COVID-19 pandemic. Our short-term results (Galdiolo et al, 2022) underlined an increase in couple satisfaction during the first weeks of the pandemic and lockdown. Considering a long-term perspective, we observed that couple satisfaction slightly changed for Relationship Dissatisfaction and did not change for Difficulties in Problem-solving Communication, Aggression, and Conflicts over Children Rearing.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Our first hypothesis was disconfirmed: There were no dramatic negative changes in couple satisfaction during 1 year of the COVID-19 pandemic. Our short-term results (Galdiolo et al, 2022) underlined an increase in couple satisfaction during the first weeks of the pandemic and lockdown. Considering a long-term perspective, we observed that couple satisfaction slightly changed for Relationship Dissatisfaction and did not change for Difficulties in Problem-solving Communication, Aggression, and Conflicts over Children Rearing.…”
Section: Discussionmentioning
confidence: 67%
“…Couples may suffer from an acute stress (i.e., the beginning of the pandemic and lockdown) that may be rather punctual, limited in time, and therefore less demanding and less exhausting for couples’ resources. The experience of an acute stressor may even be an opportunity for couples to reinforce feelings of closeness and relational efficacy, which could explain the positive influence of the first strict lockdown on couple satisfaction (Galdiolo et al, 2022). Couples may also suffer from chronic, continuing stress exposure (i.e., 1-year pandemic) that may decrease couples’ resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent longitudinal work (Galdiolo et al, 2022a(Galdiolo et al, , 2022b showed that couples reported lower levels of relationship distress during the strict lockdown, whereas after one year of pandemic, the latter returned to their baseline levels, or even increased, regardless of the duration of the relationship, the presence of children at home, or the time spent together. Consequently, we hypothesized a quadratic effect of the one-year lockdown on we-ness and separateness, i.e., with higher levels of we-ness and lower levels of separateness at the end of the strict lockdown (i.e., in comparison to the beginning of the lockdown) as the couple's response to an acute stressor, and the opposite pattern after one year of lockdown as a response to a chronic stressor.…”
Section: The Current Studymentioning
confidence: 98%
“…Many -mostly cross-sectional- studies have investigated the impact of COVID-19 on intimate relationships (for a review, see Candel & Jitaru, 2021) and found that the pandemic might indeed pose a threat to people's intimate relationships, at least in the short-term. Our recent longitudinal work revealed that in the short-term (i.e., during the strict lockdown), couples reported lower levels of relationship distress, while relationship distress increased in the long-term (i.e., after one year of the pandemic) (Galdiolo et al, 2022a, 2022b). Our data thus seem to suggest that being faced with the strict short-time lockdown -as an acute stressor- initially brought most couples together, whereas the chronic stress exposure (i.e., one-year pandemic) began to break them apart.…”
Section: Intimate Relationships During the Covid-19 Pandemicmentioning
confidence: 98%